Examination the stresseffect of litter’s let-together system (“kindergarten”) by measuring faecal cortisol metabolites of sows and piglets - Győri, Zsolt; Kulcsár, Margit; Balogh, Péter; Huzsvai, László; Novotniné Dankó, Gabriella (Acta Agraria Debreceniensis, 2016)
Piglets in commercial intensive pig husbandry are often abruptly weaned between 3 and 4 weeks for economic reasons. The process of weaning is a multifactorial stressor, in which nutritional, social, physical and psychologic stressors are combined. Piglets are often exposed to unfamiliar piglets around weaning which results in a period of vigorous fighting. Stress plays an important part in welfare research. Traditionally glucocorticoids are measured in blood samples but their use is often limited as the act of sample collection may stress an animal. Measurement of faecal cortisol/corticosterone metabolites is a non-invasive method for evaluation adrenocortical activity. The aim of this study was to examine the effect of litter’s let-together system (“kindergarten”) in the farrowing house by measuring faecal cortisol metabolites. According to our results the “kindergarten” system has no stress effect on sows and piglets, respectively.